Pests of ornamental trees, shrubs and flowers : a color handbook - Alford, D. V.; ScienceDirect eBooks (Boston : Elsevier Academic Press, 2012)
Ornamental trees, shrubs and flowers have always been extremely popular and in large demand. Whether in gardens or parks, common usage of alpines, bedding plants, cacti, cut flowers, house plants and pot plants, as well as herbaceous plants, ornamental grasses, shrubs and trees makes a definitive volume on their pests of essential value to entomologists and plant scientists. The fully revised and updated second edition of Pests of Ornamental Trees, Shrubs and Flowers follows up the successful previous edition with coverage of many new pests and highly detailed color photographs. The book opens with a review of the main features of insects, mites and other major pest groups. Each major order and family of pests is considered in turn, with details of their status, host range, world distribution, diagnostic features and biology. Descriptions of the characteristic damage caused are also given. Contains coverage of more than 60 new pests and nearly 90 additional color photographsDiscusses principles of pest control of ornamental plants, followed by sections on the various pests.
Includes bibliographical references (page 450) and index.
Title from publisher's Web site; (ScienceDirect; viewed on Sept. 4, 2012).
Elsevier
Keywords: Plants, Ornamental -- Diseases and pests -- Atlases; Plants, Ornamental -- Diseases and pests -- Identification; Plants, Ornamental -- Diseases and pests -- Handbooks, manuals, etc; Plants, Ornamental -- Diseases and pests; Electronic books